In Silico Study of the Cardioactive Constituents of Tinospora crispa (Dhaka University Journal of Pharmaceutical Sciences, 2022)
Tinosporacrispais a well-known medicinal plant utilized for hypertension. A number of studies have irrefutably established this characteristic, and there have been attempts to narrow down the possible plant constituents responsible. One of the most efficient ways of carrying out this search is the employment of in silico methods, which constitute molecular docking and interaction studies with particular endogenous macromolecular targets (assumed as receptors) using the plant compounds. Drug compound optimization can also be assisted by in silico pharmacokinetic and chemical analyses. In this study, protein and drug databases are used as the source of target and ligand libraries, respectively. AutodockVina and Discovery Studio are used for docking and interaction studies. Afterward, 6 cardioactive compounds are identified, and their potential mechanisms of action are elucidated. Later on, SwissADME and ProTox-II servers are used to assess the chemical and pharmacokinetic properties.Dhaka Univ. J. Pharm. Sci. 20(3): 293-306, 2022 (June) Centennial Special Issue